Catalytic asymmetric intermolecular [4 + 2] annulation of benzocyclobutenones with Alkynes and activated carbonyls via C—C activation - Huilai Liu; Zisong Qi; Yue Shi; Wei Wang; Fen Wang; Zhi-Wen Ding; Ai-Qun Jia; Genping Huang; Xingwei Li (Nature Communications)
Abstract The activation of C—C bonds enables rapid construction of new organic frameworks owing to facile structural reorganization. Nevertheless, enantioselective C—C activation remains heavily underexplored and has been predominantly limited to intramolecular reactions. We herein report two categories of asymmetric intermolecular [4 + 2] annulations between benzocyclobutenones (BCBs) and unsaturated reagents, namely, alkynes and cyclic dicarbonyl compounds. The atroposelective coupling of BCB with several classes of sterically hindered alkynes afford C—N and C—C axially chiral 2-naphthols. The [4 + 2] annulation of BCBs and α-dicarbonyls afford spirocyclic products. Both coupling systems proceed efficiently with excellent regio-, chemo- and enantioselectivity via substrate activation and judicious choice of chiral bidentate phosphine ligands. Synthetic transformations of selected products are demonstrated, and the derived chiral products are shown to be useful additives in C—H bond activation or as ligands in Pd-catalyzed C—C coupling.